THE OBSTACLES ANALYSIS IN THE IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT ON THE MSMES PERFORMANCE IN INDONESIA - Anggawidia Wibaselppa; R Z Abdul Aziz; Delli Maria (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The MSME must always improve the quality of their products and services in the global competition era. The achieving a performance in an organization can be seen from the organization objectives. It can be measured by quantitative or qualitative method. Total Quality Management (TQM) is a very competitive tool in improving the quality of products or services from MSMEs. This research was conducted by taking research places in MSMEs in Indonesia, especially in Lampung and Surabaya Provinces. The purpose of this study was to find out and analyze the influence of the constraints that MSMEs faced on performance. This type of research was quantitative. The populations in this study were all MSMEs in Lampung and Surabaya Provinces. The sampling technique was probability sampling. Research data was collected using documentation, questionnaires and literature study. Data analysis techniques were factor analysis and multiple linear regression with the help of SPSS data processing. The results of the study showed the resistance variables formed from latent attributes. They are two factor variables. Obstacle factor variables had proven that they have a positive and significant relationship to financial and non-financial performance, but in the partial test, it proved that only two factors had a significant positive relationship to performance with a 95% confidence level.                                          Keyword: Obstacles, Organizational Performance, Total Quality Management, Micro Small and Medium Enterprises (MSMEs)